(untitled) (African Journal of Biomedical Research, 2020)
Cancers are major contributors to mortality among women in developing countries, with patterns changing over time. This study was done to ascertain the changes in trends and patterns of breast, cervical and ovarian cancers in women over two periods of one decade each, thirty-five years apart. Data on breast, cervical and ovarian cancers in Nigerian women over the two ten-year periods were obtained from the Ibadan Cancer Registry, using a well-structured proforma with extraction of information such as age, cancer sites and year of presentation. The extracted data were analyzed and related to information provided by the International Agency for Research on Cancer (IARC). There were about 400 cases of breast, cervical and ovarian cancers from 1960 to 1969 with cervical cancer having the highest relative frequency, while about 3000 cases of these cancers were reported from 2004 to 2013, with breast cancer having the highest ratio frequency. The age group with the highest frequencies for the three cancer types from 2004 to 2013 was 40 - 49 years, while it was 60 – 69 years from 1960 to 1969. Mean ages at presentation were 48.96 ± 13.32, 54.40 ± 13.41 and 44.42 ± 16.99 years for breast, cervical and ovarian cancers respectively. Breast and cervical cancers are the two commonest cancers in Nigerian women over the five-decade period, with breast cancer overtaking cervical cancer as the most frequently diagnosed. The number of cancer cases recorded increased seven-fold and the peak age group at diagnosis of breast cancer dropped by about twenty years over the period